Exploring a Toddler’s Foreign Language Development through Watching English Videos on YouTube - Amy Fayla Sufa; Dzulfikri Dzulfikri (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This study explores the progress of a Javanese toddler’s Foreign Language (FL) development by providing a stimulus through watching English videos on YouTube. Zhaff, a non-English toddler living in Java was the subject of this study. Longitudinal observation in a case study used as the research method. The data were collected in the form of recorded videos, interviews, and notes taken from direct interaction. This research only focuses on his English and did not give the evidence on his Bahasa Indonesia development. As the results, Zhaff categorized as a bilingual child influenced by the media of YouTube. He experienced an improvement on his FL as the level of the video he watched increased. Starting with a simple vocabulary from animal songs, imitating songs from nursery rhymes, until the improvement in making some phrases and processing complex words that he got from cartoon dialogues. This study further reveals that children’s cognitive ability to acquire vocabulary is marvelous.